2004
DOI: 10.1016/s0006-3495(04)74134-x
|View full text |Cite
|
Sign up to set email alerts
|

The Connection between Chromatin Motion on the 100 nm Length Scale and Core Histone Dynamics in Live XTC-2 Cells and Isolated Nuclei

Abstract: The diffusive motion of DNA-containing chromatin in live cells and isolated nuclei is investigated using a two-photon standing wave fluorescence photobleaching experiment with 100 nm spatial resolution. The chromatin is labeled using the minor groove binding dye Hoechst 33342. In live cells, the mean diffusion rate is 5 x 10(-4) micro m2/s, with considerable cell-to-cell variation. This diffusion is highly constrained and cannot be observed in a standard, single beam fluorescence recovery after photobleaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…An image of the Hoechst 33342 stain was also acquired before and after each measurement to check for DNA movement (in those files displaying no cell movement). As reported by others (23,24), no detectable motion of the DNA was ever observed. The autocorrelation function (ACF) carpet obtained was then analyzed and pair correlation functions derived (mathematical derivation of the pCF is reported in SI Materials and Methods).…”
Section: Methodssupporting
confidence: 69%
“…An image of the Hoechst 33342 stain was also acquired before and after each measurement to check for DNA movement (in those files displaying no cell movement). As reported by others (23,24), no detectable motion of the DNA was ever observed. The autocorrelation function (ACF) carpet obtained was then analyzed and pair correlation functions derived (mathematical derivation of the pCF is reported in SI Materials and Methods).…”
Section: Methodssupporting
confidence: 69%
“…48 In contrast, nuclei isolated in inert polymers containing solution maintain their intact ultrastructure and transcription activity, 39 indicating that cytoplasmic macromolecular crowding effect is critical to maintain a more physiological condition of nuclei. Consistently, using inert polymers to mimic cytoplasmic crowding effect successfully preserved SIRT1 in the nucleus during fractionation, as it did previously for GRFI which leaked out similarly during isolation of nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…SWFM has been applied to study the diffusive motion of DNA-containing chromatin in live cells and isolated nuclei. 10 This study centred on imaging processes involving histone proteins and DNA which occurred on 100 nm length scales, something not possible using diffraction limited fluorescence microscopy. At the same time as studies using SWFM were being performed the first set of studies applying 4Pi to biosystems were also being undertaken.…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…Davis and Bardeen used two-photon SWFM to study the diffusive motion of DNA-containing chromatin in live cells and isolated nuclei. 10 The diffusion processes studied centred on understanding the interactions of histone proteins with DNA which occurred on 100 nm length scales which was accessible when imaging using two-photon SWFM. These studies demonstrated that the ultrahigh image resolution achievable using SWFM enabled better understanding of fundamental questions related to structural biology and also to protein biology.…”
Section: The Use Of Linear Processesmentioning
confidence: 99%